Informatic Analysis and Review of Literature on the Optimum Selection of Sustainable Materials Used in Construction Projects: Critical review - Abouhelal, Dina; Kamel, Wael; Bassioni, Hesham (International Journal of Sustainable Construction Engineering and Technology, 2023)
The dramatic increase in urban population has led to rapid infrastructure development worldwide and the construction industry has become one of the most progressive sectors in the world today. As a result, the construction process and its related stages play a significant role in the environment's impact, both directly (via resource and energy consumption as well as the production of contamination and waste) and indirectly (through intense pressure on inadequate infrastructures). Consequently, there is a global drive to develop “environmental- friendly and sustainable, “green” and carbon reducing buildings”. Implementing sustainability can improve the quality of our life, granting us a healthy life and promoting economic, social, and environmental circumstances. The optimal selection of sustainable building materials is acknowledged as the most fundamental way for designers to apply sustainability principles to construction projects. This Paper provides a comprehensive literature review for sustainability maximization through the material selection process. The paper performs an analysis of the previous studies related to sustainable material selection to identify the critical factors and knowledge gaps that should be considered in the material selection process. Finally, the paper concludes that the current literature in the building domain lacks a standard method that could help decision-makers select the appropriate materials by considering all factors that arise in the decision-making process to maximize sustainability in buildings. Furthermore, a need exists to fill the gap between designers and decision-makers in the sustainable construction industry for improving the selection process of sustainable building materials while at the same time looking at the accomplishment of environmental goals and meeting design and budget requirements.